Decision model for selection of modernization measures: public building case - Rasiulis, Romas; Ustinovichius, Leonas; Vilutienė, Tatjana; Popov, Vladimir (Journal of Civil Engineering and Management, 2015)
The aim of our study is to present the decision model for selection of optimal combinations of modernization measures. the presented algorithm of decision synthesis method comprises method for integrated significance determination of efficiency indicators and multiple criteria decision methods. the paper also presents the case study illustrating the application of proposed model. as the alternative modernization measures can generate many alternative combinations the decision tree model was proposed as an efficient tool facilitating the analysis of big data and included in algorithm. three multiple criteria decision support methods based on quantitative measurements included in algorithm used to increase the reliability of the decision. the proposed algorithm is very suitable for evaluation of modernization decisions of the building and enables decision-maker to select the best performing alternative in terms of energy consumption, cost of instalment and other relevant criteria.